CORE TRAINING UNDER SUSPENSION EXERCISE THERAPY ON TREATMENT OF LOW BACK PAIN - Ye,Lei (2021)
ABSTRACT Introduction: The main clinical feature of chronic nonspecific low back pain (CNLBP) is lower back pain, and suspension sports therapy has a specific effect in this case. Objective: To investigate the changes of flexion-relaxation phenomenon in patients with lower back pain after core control training of suspension exercise therapy (SET). Methods: 84 subjects who met the inclusion and exclusion criteria of chronic low back pain in this experiment were randomly divided into an experimental group and a control group. The experimental group was treated with suspension training. The control group only received acupuncture. We then determined the muscle fascia tension and core stability of the lower lumbar region. Results: The visual analog scale (VAS) and Oswestry dysfunction index (ODI) evaluations of the two groups of patients were different. Conclusion: Suspended core stabilization training has a significant long-term effect in reducing lower back pain and improving waist function in patients with chronic nonspecific low back pain. Level of evidence II; Therapeutic studies - investigation of treatment results .